Avaliação do tamanho de partícula e forma física da ração sobre o desempenho e características de carcaça de suínos machos castrados em crescimento e terminação - Ana Paula Liboreiro Brustolini (2014)
Aiming to determine the particle size and physical form of the diet to provide the best performance and carcass characteristics of barrows growing and finishing two experiments were conducted: the first experiment to determine the optimal particle size of the feed and the second trial for determine the best physical form of ration. In each experiment, 48 barrows commercial strain with initial age of 64 days and final age of 135 days were used. The experimental design was completely randomized with four treatments and six replicates of two animals composing the experimental unit in each experiment. The four treatments of experiment I were composed of mash diets particle size equal to 434μm; 614 mm; 627 m and 888 micrometers. The four treatments of experiment II were composed of: fine mash diet, coarse mash diet, fine pelleted feed and coarse pelleted feed. Observation periods in both experiments, were: phase 1 (phase of growth, of 64 to 104 days) and phase 2 (phase growerfinisher, of 64 to 135 days). The diets used in the experiments were isocaloric and isonitrogenous, formulated to meet the nutritional requirements of animals at each stage. In the first experiment there was a linear effect (p <0,10) for feed conversion were evaluated in both phases, the particle size of the feed equal to 434 μm improved feed conversion were 4,0% in phase 1 and 8.5 % in phase 2, there was a linear effect (p <0,10) for loin depth according to the particle size of the feed for stage 1 and made quadratic (p <0,10) in phase 2, where the size of particle equal to 434 μm gave the best values for this data. In experiment II increased (p <0,10) 5,0% of the final weight of animals and 6,8% increase (p <0,10) in average daily weight gain with the use of pelleted feed in thin phase 1, at the same stage the pelleted diet, whether it be coarse or fine provided 11,0% improvement (p <0,10) feed conversion, backfat thickness was greater (p <0.10) for hand fed animals with mash diet and depth of rib was greater (p <0,10) for the animals hand fed with coarse mash diet compared to the other treatments, in phase 2 the final weight increased (p <0,10) by 5,0% and the average weight gain of the animals increased (p <0,10) by 8,5% with the use of thin pelleted feed, pelleted feed, whether it be thin or thick decreased (p <0,10) consumption average daily animal and improved in 11,0% (p <0,10) feed conversion of animals by 14,0%. Based on this experiment, the optimum particle size for growing and finishing pigs is 434 μm and the best physical form of ration is pelleted.